MORPHO-STYLISTIC ANALYSIS OF CRISIS MOTIVATED WORDS IN ONLINE NEWSPAPER HEADLINES OF KOGI STATE ELECTION OF 2019 - Ekwueme, Joekin; Samaila Bitrus, Zubairu; Jesmiel, Kefas; Lekyong, Victoria (Advances in Social Sciences Research Journal, 2020)
Words could both be an instrument of war and peace. Journalists could build a nation and at the same time destroy what has been built over the years by the means of language. This study, therefore, investigated the morpho-stylistics of crisis motivated words in online newspaper headlines of Kogi State election of 2019. The purpose of the study was to identify and explain morpho-stylistically the linguistic features dominant in such discourse that motivate or trigger crisis. The study was anchored on Halliday’s (1984) aspects of Language Stratification of SFG. The corpuses of the study which comprised ten headlines were collected at random from ten online news platforms. The items were analyzed in accordance with the tenets of Language Stratification of SFG. The findings revealed that the morphological formations dominant in the headlines that are capable of motivating crisis were compounding and neologisms or coinages; and those formations mark the style of the editors/authors. It is concluded that words could indeed trigger crisis if not properly managed. It is, therefore, recommended that editors and authors should select their words carefully before publishing in order to avert the unforeseen crisis.